A review of medical error taxonomies: a human factors perspective - Taib, Ibrahim Adham; McIntosh, Andrew Stuart; Caponecchia, Carlo; Baysari, Melissa T. (Elsevier Science BV, 2011)
Although a large number of medical error taxonomies have been published, there is little evidence to suggest that these taxonomies have been systematically compared. This paper describes a study comparing 26 medical error taxonomies using a human factors perspective. The taxonomies were examined to determine if they classified systemic factors of medical errors and if they utilized theoretical error concepts in their classifications. Scope of classification was also examined. It was found that two-thirds of the taxonomies classified systemic factors of medical errors and only a third utilized theoretical error concepts. Medical error taxonomies based on theoretical error concepts were more likely to be generic in applicability and also more likely to classify systemic factors and psychological error mechanisms of medical errors. In addition to terminology, the medical error taxonomies also varied in terms of domain-specificity, granularity, and developmental process. Different medical error taxonomies provide different information; how these differences affect medical error management needs to be investigated.